Gender differences regarding barriers and motivators of HIV status disclosure among HIV-positive service users - Kebede Deribe; Kifle Woldemichael; Bernard Joseph Njau; Bereket Yakob; Sibhatu Biadgilign; Alemayehu Amberbir (Taylor & Francis Group, 2010)
There are inconsistent findings about the relation between gender and HIV status disclosure. We conducted a facility-based cross-sectional study, using qualitative and quantitative data collection methods, to explore gender differences in HIV-positive status disclosure among service users in south-west Ethiopia. Among 705 participants, an equal number of men and women (94.6% men v. 94.3%, women) indicated that they had disclosed their result to someone, and the majority (90.9% men v. 90.7% women) to their current main partner. 'It is customary to tell my partner everything' was the most frequently cited reason for disclosing (62.5% men v. 68.5% women). Reasons for non-disclosure varied by gender: men were concerned about their partner's worry and exposure of their own unfaithfulness. Women feared physical violence, and social and economic pressure in raising their children. Factors that influenced disclosure also indicated gender variation. For men, disclosure of HIV results to a sexual partner was positively associated with knowing the partner's HIV status and discussion about HIV testing prior to seeking services, while for women it was associated with knowing the partner's HIV status, advanced disease stage, having no more than primary education, being married, and perceiving the current relationship as long-lasting.There was no significant difference in the proportion of HIV status disclosure among men and women. However, the contextual barriers and motivators of disclosure varied by gender. Therefore it is important that clinicians, counsellors, and health educators underscore the importance of gender-specific interventions in efforts to dispel barriers to HIV status disclosure.